KESALAHAN PENGUCAPAN VOKAL DEPAN BAHASA INGGRIS OLEH MAHASISWA SEMESTER I UNIVERSITAS NASIONALTIMOR LOROSAâ€™E - Rosa Da Costa Tilman; Ika Nurhayani (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2015)
In the process of English learning either as foreign language or second language, several students still encounter some problems in pronouncing English front vowels. This study is aimed at describing the pronunciation errors of front vowels done by the first semester students of Timor Loorosaâ€™e National University in Timor Leste. This study used descriptive qualitative approach. The technique of data collection was conducted by recording the English front vowels minimal pairs pronounced by the students and the Portugese native speakers, then they were compared with the ones of English native speakers. The results of the recording were verified by the spectogram to know the F1 and F2 forman produced by each participant in Praat software. The focus of this study are four English front vowels /i/, /I/, /Ô/ dan /Ã¦/. The results showed that the student and Portugese native speaker pronunciations of English front vowels are different from the standart pronounced by the English native sspeakers. The examples are in the words beat/bit/ - bit/bIt/ and bed/bÔd/ - bad/bÃ¦d/. The problems occuring in this study are caused by sound and grammar interference that influence the English vowel pronunciation of the students. Based on the results of this study, it can be concluded that the students still have problems inpronouncing English front vowels because they are influenced by the pronunciation system of Portugese.Keywords: English front vowels, language interference, pronunciation errors, the first semester students Timor Lorasaâ€™e National University.